Slave Women in the New World Gender Stratification in the Caribbean - Morrissey, Marietta (University Press of Kansas, 1989)
In this innovative study, Marietta Morrissey reframes the debate over slavery in the New World by focusing on the experiences of slave women. Rich in detail and rigorously comparative, her work illuminates the exploitation, achievements, and resilience of slave women in the British, Dutch, French, Spanish, and Danish colonies in the Caribbean from 1600 through the mid 1800s.Morrissey examines a wide spectrum of experience among Caribbean slave women, including their work at home, in the fields, and as domestics; their roles as wives and mothers; their health, sexuality, and fertility; and their decline in status with the advent of industrialization and the abolition of slavery.Life for these women, Morrissey shows, was much more hazardous, brutal, and fragmented than it was for their counterparts in the American South. These women were in a constant, dynamic struggle with men-both masters and fellow slaves-over the foundations of their social experience. This experience was defined both by their status as slaves and by gender inequality. On the one hand, their slave status gradually robbed them of their domain-the household economy-and created a kind of perverse equality in which slave women-like slave men-became "units of agricultural labor." One the other hand, slave women were denied the access that slave men eventually gained to skilled agricultural work. The result of this gender inequality, as Morrissey convincingly demonstrates, was a further erosion of the status and authority of slave women within their own culture.Morrissey's study, which addresses significant issues in women's history and black history, will go far toward reshaping our perceptions of slave life in the new world.